Implementation of the Independent Curriculum in the Pancasila Student Profile at Driving Schools - Sri Bimo, Djoko; Mustofa, Triono Ali; Anggraini, Fadhilla Nangroe (Bulletin of Science Education, 2024)
The research illustrates the implementation of the independent curriculum in the profile of Pancasila students in driving schools. This research aims to see how the implementation of the independent curriculum based on the Pancasila student profile and the role of driving schools in the implementation of the independent curriculum. This research uses qualitative methods with a literature study approach through collecting information in the form of journals, books, mass media, and so on both physical and nonphysical. The results of the study explained that, the implementation of the existing Pancasila student profile in the independent curriculum there is a project developed based on the theme set by the government, through the Pancasila student profile program is expected to become individuals who have good morality, are able to compete both at the national and global levels, and have the ability to work together to develop creative ideas and most importantly make students able to apply the profile dimension Pancasila students in everyday life. The driving school is one of the axes of the implementation of the independent curriculum that has been implemented, the principal and teachers are trying to maximize the school's role as an education developer and grow all the potential contained in students. Keywords: Merdeka Curriculum, Pancasila Student Profile, Mover School